Analisis Framing Pemberitaan Kawal Putusan MK pada Kompas.com - Sartika, Cintya Dewi; Anshori, Dadang S.; Kusumah, Encep (Jayapangus Press, 2025)
This research is motivated by the importance of using precise and unambiguous language so that it can be well understood by the public. The data of this study were taken from political news uploaded by Kompas.com during August 21-23, 2024 related to the Constitutional Court's decision Number 70/PUU-XXII/2024 regarding the minimum age limit for regional head candidates. The aim is to analyze the media framing in reporting the issue using the Zhongdang Pan & Gerald M. Kosicki framing analysis model. The results of the analysis found several terms that describe uncertainty and critical terms to emphasize the social impact of dynastic politics and political interests that benefit certain parties. Uncertainty is a framing raised by Kompas.com to form a narrative of transparency related to the unfinalized legal process and create a discourse of public supervision highlighted through the “Kawal Putusan MK” narrative. The reaction of public protests is an important consideration, especially for Kompas.com, which can strengthen the narrative of political favoritism carried out by the DPR, which is considered to open the way for dynastic politics for Kaesang, who has prepared himself by taking care of the letters related to the requirements for the 2024 Pilkada candidates.